2014
DOI: 10.1016/j.atmosenv.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid approach for estimating total deposition in the United States

Abstract: h i g h l i g h t sA novel approach was developed to produce estimates of total nitrogen and sulfur. The approach merges data from measurements and models. Measurement data have greater weight near monitoring sites. Modeled data are used for deposition species that are not measured. This total deposition data set is useful for ecological assessments. a r t i c l e i n f o b s t r a c tAtmospheric deposition of nitrogen and sulfur causes many deleterious effects on ecosystems including acidification and excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 28 publications
6
130
1
Order By: Relevance
“…The maximum regional average inorganic N deposition flux (12.1 kg N/ha per year) was observed in the Upper Midwest region (IV); relatively large deposition fluxes were also observed for California and the eastern United States. These spatial patterns are similar to those identified in recent model simulations (43).…”
Section: Fractional Reduced N Contributions To the Total Inorganic N supporting
confidence: 76%
“…The maximum regional average inorganic N deposition flux (12.1 kg N/ha per year) was observed in the Upper Midwest region (IV); relatively large deposition fluxes were also observed for California and the eastern United States. These spatial patterns are similar to those identified in recent model simulations (43).…”
Section: Fractional Reduced N Contributions To the Total Inorganic N supporting
confidence: 76%
“…The spatial distribution of reduced and oxidized Nr deposition is comparable with other studies (Zhang et al, 2012;Du et al, 2014;Schwede and Lear, 2014) yet a few differences and uncertainties are worth considering. Du et al (2014) found greater wet deposition of NH + 4 compared to wet deposition of NO − 3 over the contiguous US except in the Northeast region.…”
Section: Evaluation Of Simulated Nr Depositionsupporting
confidence: 70%
“…This suggests that oxidized Nr may be overestimated in our study. Schwede and Lear (2014) generated maps of Nr deposition for multiple years, including 2010. These maps display localized hotspots in parts of Colorado and Idaho that are not evident in our results.…”
Section: Evaluation Of Simulated Nr Depositionmentioning
confidence: 99%
“…Each study reports 2 years of locally measured annual averages for a total of 8 data points. For reference, we compared these local data with estimates for Lake Mattamuskeet in 2012 (the most recent year of available data) using a hybrid method that incorporates both wet and dry deposition (Schwede and Lear 2014). We found that the mean of local measurements (5.1 kg N ha…”
Section: Atmospheric Depositionmentioning
confidence: 99%